2013
DOI: 10.4081/nd.2013.e1
|View full text |Cite
|
Sign up to set email alerts
|

Effect of nanoparticles suspension on the growth of mung (Vigna radiata) seedlings by foliar spray method

Abstract: The present experimental investigation demonstrates the effect of nano-ZnO, nanoFeO and nano-ZnCuFe-oxide particles on the growth of mung (Vigna radiata) seedling. The study was carried out by spraying optimum concentrations of nanoparticles in suspension form on hydroponically grown test units and examining the effect on the shoot growth of seedlings. Based on biomass assay, it was found that the seedlings displayed good growth over control, demonstrating a positive effect of the nanoparticle treatment. The b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
40
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 165 publications
(53 citation statements)
references
References 18 publications
(17 reference statements)
7
40
0
1
Order By: Relevance
“…(2014) and Amirnia et al (2014), those who reported significant improvements in various growth parameters by adding Fenanoparticles. Similar results were obtained by Ghafari & Razmjoo (2015) in durum wheat; Dhoke et al (2013) in mung (Vigna radiate); Mohamadipoor et al (2013) in Spathyphyllum illnsion and Soliman et al (2015) in Moringa peregrine. It was also reported that fruit yield of Solanum melanogena L. increased by foliar application of nano -iron chelate fertilizer (Bozorgi, 2012).…”
Section: Discussionsupporting
confidence: 79%
“…(2014) and Amirnia et al (2014), those who reported significant improvements in various growth parameters by adding Fenanoparticles. Similar results were obtained by Ghafari & Razmjoo (2015) in durum wheat; Dhoke et al (2013) in mung (Vigna radiate); Mohamadipoor et al (2013) in Spathyphyllum illnsion and Soliman et al (2015) in Moringa peregrine. It was also reported that fruit yield of Solanum melanogena L. increased by foliar application of nano -iron chelate fertilizer (Bozorgi, 2012).…”
Section: Discussionsupporting
confidence: 79%
“…In addition, nanoferti- 6 simplify their absorption in plants (Dhoke et al, 2013). Mahmoodzadeh et al (2013) reported that direct exposure of wheat plants to specific types of nanoparticles cause significant increase in all growth variables determined at optimum concentrations of nanosolution.…”
Section: Discussionmentioning
confidence: 99%
“…The selective uptake, biotransformation, and translocation of various nanoparticles by a model plant have been schematically represented (Dhoke et al, 2013). Nanoparticles have high reactivity because of more specific surface area, more density of reactive areas, or increased reactivity of these areas on the particle surfaces.…”
Section: Discussionmentioning
confidence: 99%
“…These chemicals result in various side effects in the plants and soil, and harm the environment in different ways. Nano-ZnO particle (20 nm), nano-FeO (100 nm), and nano-CuO (40 nm) at ppm level showed increased shoot and root length in Mung seedling by foliar spray (Dhoke et al 2013). Foliar spray method is more practical for an agronomic standpoint as plants can absorb essential elements through their leaves more efficiently compared to root feeding.…”
Section: Introductionmentioning
confidence: 97%